'Infinity Means it Goes on Forever': Siblings' Informal Teaching of Mathematics. Issue 2 (24th August 2015) - Howe, Nina; Adrien, Emmanuelle; Della Porta, Sandra; Peccia, Stephanie; Recchia, Holly; Osana, Helena P.; Ross, Hildy
Abstract : Sibling‐directed teaching of mathematical topics during naturalistic home interactions was investigated in 39 middle‐class sibling dyads at two time points. At time 1 (T1), siblings were 2 and 4 years of age, and at time 2 (T2), siblings were 4 and 6 years of age. Intentional sequences of sibling‐directed mathematical teaching were coded for (i) topics (e.g., number), (ii) contexts (e.g., play with materials/toys), and (iii) type of knowledge (conceptual and procedural). Siblings engaged in teaching number, geometry, and measurement at T1 and demonstrated preliminary evidence of teaching of grouping, relations, and operations at T2. Regarding context, at T1, mathematical teaching occurred most frequently during play with materials/toys, while at T2, games with rules were prominent. Teaching of conceptual or procedural knowledge varied over time and by topic and context. Findings are discussed in light of recent work on understanding children's mathematical knowledge as it develops in the informal family context. Copyright © 2015 John Wiley & Sons, Ltd.